2012
DOI: 10.1097/bsd.0b013e318220dbe9
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoplasty is Effective in Reducing Both Mechanical and Radicular Low Back Pain

Abstract: We concluded that the nucleoplasty technique is a safe and effective procedure for radicular or combined radicular and mechanical low back pain and should be used in selected cases before open surgery after conservative treatment has failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Three recent prospective observational studies by Karaman et al., Shabat el al., and Azzazi et al . again showed that there were good short‐term and long‐term results for nucleoplasty, even up to 2 years.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Three recent prospective observational studies by Karaman et al., Shabat el al., and Azzazi et al . again showed that there were good short‐term and long‐term results for nucleoplasty, even up to 2 years.…”
Section: Resultsmentioning
confidence: 91%
“…Three recent prospective observational studies by Karaman et al, Shabat el al., and Azzazi et al [45][46][47] again showed that there were good short-term and longterm results for nucleoplasty, even up to 2 years. A study by Ogbonnaya et al 48 was the only recent study showing poor results for nucleoplasty.…”
Section: Nucleoplastymentioning
confidence: 98%
“…Later, the efficacy data of cobation nucleopalsty in treating contained disc herniation with associated symptoms were reported by a series of clinical studies. 19 – 23 However, the efficacy data of nucleoplasty for lumbar discogenic pain was rare. 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…6 The clinical effectiveness of disk decompression using plasma energy such as nucleoplasty and L'DISQ (U&I Corp., Uijeongbu, South Korea) has been proven in many studies. [7][8][9] However, experimental data supporting the effectiveness of tissue removal and safety of plasma ablation are insufficient. In clinical settings, major variables in the plasma procedure such as voltage of electrical output and speed of procedure tip movement largely rely on the surgeon's personal or collective experience.…”
Section: Introductionmentioning
confidence: 99%